Implementation of Hajj with Bailout Funds with the Al Qardh Agreement - Subkhi Subkhi (Universitas Islam Sultan Agung, 2020)
This study seeks to answer the question of whether it is permissible for someone to register Hajj with bailout funds from a financial institution so that the Hajj can be carried out while the body is still healthy, as well as what factors benefit both parties and are there any difficulties faced by both of them (Bank and service users). This study used a sociological juridical approach. The type of research used was descriptive research, data collection using library documentation methods, observation and interviews. The data analysis used a qualitative descriptive method.This issue has been answered by the MUI National Sharia Council with fatwa number 29 / DSN-MUI / 2002 regarding the financing of Hajj services by the Islamic financial institution. On that basis, many prospective pilgrims have registered through the haj bailout service of Islamic financial institutions. The form of Hajj bailout services is not a commercial transaction that prioritizes profit as the motivation, but is a service of virtue with the aim of helping people who need help.Key words: hajj; Hajj bailout fund; al qardh wal ijarah; virtue